Getting started with MATLAB 7 : a quick introduction for scientists and engineers - Pratap, Rudra (New York : Oxford University Press, 2006)
Engineering
Keywords: MATLAB; MATLAB windows; Interactive computation; Matrix and vectors; Programming in MATLAB; Graphics; MATLAB language